2016
DOI: 10.1002/aur.1714
|View full text |Cite
|
Sign up to set email alerts
|

Auditory processing in noise is associated with complex patterns of disrupted functional connectivity in autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is associated with difficulty in processing speech in a noisy background, but the neural mechanisms that underlie this deficit have not been mapped. To address this question, we used magnetoencephalography to compare the cortical responses between ASD and typically developing (TD) individuals to a passive mismatch paradigm. We repeated the paradigm twice, once in a quiet background, and once in the presence of background noise. We focused on both the evoked mismatch field (MMF) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 103 publications
(125 reference statements)
3
53
0
Order By: Relevance
“…According to the results of functional characterization, the maMTG.R was highly associated with hearing and language, which are two vital components of auditory processing. Although many researchers identified auditory processing deficits in adults with ASD and hypothesized that there is a common disruption in the neural network associated with auditory processing in ASD [Bomba & Pang, 2004;Mamashli et al, 2017;Marco, Hinkley, Hill, & Nagarajan, 2011;Schwartz, Shinn-Cunningham, & Tager-Flusberg, 2018], the main brain regions involved in the network are still an open question. Our findings provide evidence that the disruptions of the maMTG.R might be associated with auditory processing deficits in adults with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of functional characterization, the maMTG.R was highly associated with hearing and language, which are two vital components of auditory processing. Although many researchers identified auditory processing deficits in adults with ASD and hypothesized that there is a common disruption in the neural network associated with auditory processing in ASD [Bomba & Pang, 2004;Mamashli et al, 2017;Marco, Hinkley, Hill, & Nagarajan, 2011;Schwartz, Shinn-Cunningham, & Tager-Flusberg, 2018], the main brain regions involved in the network are still an open question. Our findings provide evidence that the disruptions of the maMTG.R might be associated with auditory processing deficits in adults with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, multiple comparisons within each of the sub‐ROIs are accounted for by the cluster analysis in time and frequency (Step 1) and by the permutations approach (Step 2, 3) for the sub‐ROIs tests. Please see (Mamashli et al, ) for more details on this method. Matlab scripts are available online through our github repository (https://github.com/fm897/NSR).…”
Section: Methodsmentioning
confidence: 99%
“…Autism spectrum disorder is a neurodevelopmental disorder commonly associated with verbal and communicative dysfunctions (Mcdaniel et al, 2018). In three studies identified in this review, alteration of language task-related coherence was associated with ASD (Righi et al, 2014;Kovelman et al, 2015;Mamashli et al, 2017). However, no direct association was made with language functioning.…”
Section: Results From Coherence In Clinical Populationmentioning
confidence: 86%
“…Finally, Mamashli et al (2017) used an MEG tonal mismatch paradigm in children (9-15 years old) with ASD. The MEG recording revealed an increase in frontotemporal coherence in the ASD group relative to the TD group, in response to both standard and deviant stimuli.…”
Section: Results From Coherence In Clinical Populationmentioning
confidence: 99%
See 1 more Smart Citation